THE EFFECT OF E-COMMERCE TAX SOCIALIZATION AND E-COMMERCE TAX RATES ON ONLINE-BASED UMKM TAX COMPLIANCE WITH TAX AWARENESS AS A MEDIATION VARIABLE - Arvianita, Azizah Cahya; Sulhendri (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2026)
This study aims to analyze the influence of e-commerce tax socialization and e-commerce tax rates on tax compliance among online-based UMKM’s, with tax awareness as a mediating variable. The research adopts a quantitative approach using an explanatory survey design. Primary data were collected through structured questionnaires distributed to online-based UMKM taxpayers in Kebayoran Baru, South Jakarta. From a population of 150 UMKM taxpayers, a sample of 110 respondents was determined using the Slovin formula with a 5% margin of error. Data collection was conducted from December 2024 until the completion of the study. Data were analyzed using path analysis to examine both direct and indirect relationships among variables. The results are expected to demonstrate that e-commerce tax socialization has a positive influence on tax awareness and tax compliance among UMKMs. E-commerce tax rates are expected to influence tax compliance, both directly and through increased tax awareness. Furthermore, tax awareness is projected to play a significant role as a mediating variable, strengthening the relationship between tax socialization, tax rates, and tax compliance among online UMKMs. The findings of this study provide theoretical contributions regarding the tax behavior of UMKMs in the digital era and practical recommendations for the government to improve the effectiveness of tax education and optimize tax revenue from the online UMKM sector.